2019
DOI: 10.1002/1873-3468.13477
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific phosphorylation of villin remodels the actin cytoskeleton to regulate Sendai viral glycoprotein‐mediated membrane fusion

Abstract: Connivance of cellular factors during virus‐host cell membrane fusion is poorly understood. We have recently shown that cellular villin plays an important role during membrane fusion of reconstituted Sendai virosomes with hepatocytes. Here, we employed villin‐null Chinese Hamster Ovary (CHO) cells, where villin expression led to an increased fusion with virosomes, which was further enhanced due to tyrosine phosphorylation in the presence of c‐src. However, the villin RRI mutant, lacking actin‐severing function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Thisunilamellar vesicle is spherical in shape with an average diameter of ~150nm.The main characteristic of the virosomes is the retention of the most useful viral cover of glycoproteins,i.e., Influenza virus haemagglutinin (HA) and neuraminidase (NA) then they are inserted into the Phosphatide bilayer membrane. They are represented by short surface projections with a size of 15nm [27]. Research has found that to attain the desired therapeutic effect, a physical attachment between the target antigen and the virosomal carrier is necessary.…”
Section: Composition Of Different Reconstituted Virosomesmentioning
confidence: 99%
“…Thisunilamellar vesicle is spherical in shape with an average diameter of ~150nm.The main characteristic of the virosomes is the retention of the most useful viral cover of glycoproteins,i.e., Influenza virus haemagglutinin (HA) and neuraminidase (NA) then they are inserted into the Phosphatide bilayer membrane. They are represented by short surface projections with a size of 15nm [27]. Research has found that to attain the desired therapeutic effect, a physical attachment between the target antigen and the virosomal carrier is necessary.…”
Section: Composition Of Different Reconstituted Virosomesmentioning
confidence: 99%
“…Phosphorylation of tyrosine residues within the villin core promotes actin severing and bundling by three ways. First by decreasing the binding affinity to F actin, second by inhibiting the addition of new actin monomers and finally severing the preexisting actin filaments [90]. This increases the fluidity of the cytoskeleton and affects its mechanical properties enhancing cell motility in cancer.…”
Section: Villinmentioning
confidence: 99%